Learning grammar the fun way using EGGA (English grammar guide app) - Abdul Talip, Abdul Hadi; Ibrahim, Sueb; Metom, Lilly; Bohari, Zubaidah (Universiti Teknologi MARA, Kedah, 2023)
EGGA (English Grammar Guide App) is a mobile application designed as a self-directed evaluation tool that enables learners to learn basic English grammar and self-evaluate. The application provides learners with some learning materials and allows them to take quizzes via mobile devices or tablets with the Android operating system. Currently, three categories of learning materials are available; parts of speech in English, tenses, and subject-verb agreement, which are organized on a digital bookshelf. For each category, comprehensive short notes with simple examples are provided. Once learners have completed the self-instruction phase, they may self-evaluate their own comprehension of the three grammatical categories by taking a quiz. There will be ten (10) multiple-choice questions (MCQ) for each category and there is no time limit for completion of the quiz. However, only a single attempt is allowed for each question and all the ten questions must be answered sequentially. A short performance report which contains the score and grade will be displayed at the end of the quiz. This mobile application promotes self-directed learning, provides immediate feedback, makes learning fun and interactive, as well as enables learners to do self-assessment. Hence, learners will find it relatively easy to relate to and engage in the activities and exercises provided. The findings revealed that using EGGA in grammar learning can motivate learners to acquire and improve their grammar skills, as well as create a fun and interactive learning experience for them. EGGA also provides a mechanism for learners to gauge their own level of grammar competence. It is found as a useful and practical tool that can be used by learners of any age group to learn the target grammar.